Corporate Social Responsibility, Internationalization and Politics. The Case of the «Swans’ Conflict» in Valdivia, Chile - Delamaza, Gonzalo (2012)
Departing of a case study, this paper deals with changes in the so-called corporate social responsibility discourse when social conflicts get worsen and demand changes in corporations’ attitude. How are business tendencies related to social conflicts about corporations’ role in the community? During Chile’s democratic transition, between 1990 and 2010, social conflicts where fenced to punctual situations, economic growth was kept in a frame of political stability, civil society was broken and big corporations counted mostly with high social legitimacy (Delamaza 2010). The case of the swans’ death in Río Cruces, attributed to pollution produced by a cellulose refinery, catalyzed the general adoption of a corporate social responsibility discourse by representatives of Chilean big corporations. It is stated that the transforming impact of the case was due to the deep transnationalization of a large portion of Chilean business companies and the evolution of the democratic political transition, endorsing the thesis supported by Agüero (2002) about corporate social responsibility’s «context-dependant» character.